Happiness and Productivity - Oswald, Andrew J.; Proto, Eugenio; Sgroi, Daniel (Journal of Labor Economics, 2015)
Some firms say they care about the well-being and ‘happiness’ of their employees. But are such claims hype, or scientific good sense? We provide evidence, for a classic piece-rate setting, that happiness makes people more productive. In three different styles of experiment, randomly selected individuals are made happier. The treated individuals have approximately 12% greater productivity. A fourth experiment studies major real-world shocks (bereavement and family illness). Lower happiness is systematically associated with lower productivity. These different forms of evidence, with complementary strengths and weaknesses, are consistent with the existence of a causal link between human well-being and human performance.